Plant defense against leaf herbivory based on metal accumulation: examples from a tropical high altitude ecosystem - Ribeiro, Sérvio P.; Londe, Vinícius; Bueno, Amauri P.; Barbosa, Juliana S.; Corrêa, Tatiana L.; Soeltl, Tatiana; Maia, Márcia; Pinto, Victor D.; França Dueli, Grazieli; Sousa, Hildeberto Caldas; Kozovits, Alessandra R.; Nalini, Hermínio A. (Plant species biology, 2017)
Species that evolved in high‐altitude grasslands, where soils are dystrophic and metal rich, developed adaptations for these extreme conditions, such as metal accumulation and sclerophyllous leaves, and these adaptations may secondarily affect insect herbivory activity. The present study investigates the hypothesis that costs related to accumulation of certain metals may be evolutionarily compensated for by decreasing leaf herbivory in some plant species from rupestrian fields. Studies were conducted in different locations at the Ferriferous Quadrangle, a metal‐rich region in south‐east Brazil, with four species adapted to high‐altitude grasslands: Eremanthus erythropappus, Eremanthus incanus, Lychnophora ericoides and Byrsonima variabilis. Sample design varied according to population sizes and spatial distribution of individuals. We found that concentrations of manganese (Mn) and iron (Fe) significantly reduced the herbivory in the leaves of E. erythroppapus and E. incanus, whereas aluminum (Al) reduced herbivory in L. ericoides, and Mn affected negatively the herbivory in B. variabilis. These results support the hypothesis that metal‐accumulating plants, as a response to the harsh environment in which they evolved, are protected against foliar damage caused by insect herbivores in rupestrian fields. The accumulation of metals by plants at the Ferriferous Quadrangule, south‐eastern Brazil, protects them against leaf herbivory.